Analysis of iodinated quorum sensing peptides by LC-UV/ESI ion trap mass spectrometry - Yorick Janssens; Frederick Verbeke; Nathan Debunne; Evelien Wynendaele; Kathelijne Peremans; Bart De Spiegeleer (Elsevier, 2018)
Five different quorum sensing peptides (QSP) were iodinated using different iodination techniques. These iodinated peptides were analyzed using a C18 reversed phase HPLC system, applying a linear gradient of water and acetonitrile containing 0.1% (m/v) formic acid as mobile phase. Electrospray ionization (ESI) ion trap mass spectrometry was used for the identification of the modified peptides, while semi-quantification was performed using total ion current (TIC) spectra. Non-iodinated peptides and mono- and di-iodinated peptides (NIP, MIP and DIP respectively) were well separated and eluted in that order. Depending on the used iodination method, iodination yields varied from low (2%) to high (57%).